Retaining of Frequency in Micro-grid with Wind Turbine and Diesel Generator - Chung, P. D. (Engineering, Technology & Applied Science Research, 2018)
This paper aims to compare the performance of frequency regulation with two control modes of controller including power control scheme and rotor speed control scheme. The frequency control in this research is based on the frequency droop control method but fuzzy logic is used to define the frequency droop coefficient. To compare the performance of these control modes, a simulation of a micro-grid with the existence of a group of doubly fed induction generator wind turbine system and a diesel generator is fulfilled in Matlab/Simulink. Simulation results indicated that the frequency in the micro-grid with two control schemes always remains in the operation range. With the power control scheme, the frequency in the micro-grid is smoother than that with the rotor speed control. Additionally, DFIG wind turbine with the power control scheme has a better performance in terms of electrical energy when compared to the rotor speed control scheme, and hence the cost of fuel used by diesel is less costly.